Long range [compact disc, unabridged] - Box, C. J. (Box, C. J. Joe Pickett novel, 2020)
Assisting an investigation into a fatal grizzly attack that is not what it seems, Joe Pickett becomes embroiled in the case of a prominent judge's wife wounded by a would-be assassin who was shooting from a confoundingly long distance.